Age of Social Loneliness: Depression and Suicidal Ideation among Undergraduate Medical Students - Kamran Pervez Mir, Ali Zain, Ali Shakeel, Muhammad Maqsood, Tariq Iqbal, Naveed Iqbal, Noor Fatima, Umar Farooq Dar, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: In an era of social media, the social fabric is changing day by day. The current generation of medical undergraduates have to fight in multiple dimensions and they find themselves overwhelmed. Objective: To determine the suicidal ideation and depression in medical undergraduate students at public sector medical colleges. Methodology: This descriptive study was carried out this study at Gujranwala Medical College, Gujranwala and Khawaja Muhammad Safdar Medical College, Sialkot from 1st September 2023 to 31st October 2023 and 253 medical students using self-administered, prevalidated questionnaire in two public sector medical colleges were enrolled. The tool contained the Patient Health Questionnaire (PHQ-9) and Suicidal Behavioral Questionnaire (SBQ) along with demographic data. PHQ-9 is a screening tool for measuring depression and consists of nine item scale. Results: One hundred and eighty nine (74.7%) medical students have no or mild depression, 35 (13.8%) have moderate depression and 29 (11.5%) have severe depression. Using SBQ, 210(83%) students have no suicidal tendency while 43 (17%) have suicidal tendency. Most of the medical students facing moderate-severe level of depression were not seeking any psychiatric treatment. Both depression and suicidal ideations are strongly correlated. Conclusion: The depression is moderately high among medical undergraduates and it is associated with suicidal ideation. Wellness clinics are the need of time and underscore the necessity of providing higher risk population, an efficient mental health awareness and therapeutic services. Keywords: Depressive disorder, Depression, Anxiety, Stress, Undergraduate medical teaching